2021
DOI: 10.1038/s41564-020-00839-y
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of genetic diversity on gene essentiality within the Escherichia coli species

Abstract: Bacteria from the same species can differ widely in their gene content. In E. coli, the set of genes shared by all strains, known as the core genome, represents about half the number of genes present in any strain. While recent advances in bacterial genomics have enabled to unravel genes required for fitness in various experimental conditions at the genome scale, most studies have focused on model strains. As a result, the impact of this genetic diversity on core processes of the bacterial cell largely remains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 98 publications
12
94
0
Order By: Relevance
“…The set of essential genes we tested here comprises 504 protein-coding genes (S2 Table ); of those, 394 protein-coding genes were identified as essential in E. coli K-12 under standard laboratory conditions via gene knockout [24] or transposon mutagenesis [25]. Additional 110 proteincoding genes were identified as essential in a collection of 18 E. coli isolates by CRISPR interference of gene expression ( [18]; only genes identified as essential in at least one out of the three tested growth media were included; S2 Table ). Searching for plasmid-encoded homologs to the essential genes using sequence similarity revealed that only 17 (3%) of the essential genes had a homolog on plasmids (Fig 1A and Table 1).…”
Section: Essential Genes Are Rarely Encoded On Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of essential genes we tested here comprises 504 protein-coding genes (S2 Table ); of those, 394 protein-coding genes were identified as essential in E. coli K-12 under standard laboratory conditions via gene knockout [24] or transposon mutagenesis [25]. Additional 110 proteincoding genes were identified as essential in a collection of 18 E. coli isolates by CRISPR interference of gene expression ( [18]; only genes identified as essential in at least one out of the three tested growth media were included; S2 Table ). Searching for plasmid-encoded homologs to the essential genes using sequence similarity revealed that only 17 (3%) of the essential genes had a homolog on plasmids (Fig 1A and Table 1).…”
Section: Essential Genes Are Rarely Encoded On Plasmidsmentioning
confidence: 99%
“…In the second route, termed stability first, a plasmid that initially evolved a stable reproduction cycle may subsequently evolve into an essential plasmid following an essential gene gain. Notwithstanding, as essential genes are typically encoded in the chromosomes [18], the presence of an essential gene on a plasmid may be comparable to the effect of gene duplication. In addition, the expression level of plasmid-encoded genes may be amplified following an increase in plasmid copy number (e.g., [19]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we performed a semi-quantitative comparison with experimental gene knockout data of E. coli K12 MG1655 [ 37 ] in three different nutrient environments. The approach is described in Materials and Methods with resulting data in Fig C in S1 Text .…”
Section: Resultsmentioning
confidence: 99%
“…We compared the computational single-gene knockout phenotype predictions for the different biomass compositions with experimental data from Rousset et al [ 37 ] for E. coli K12 MG1655 grown in three different media: minimal, rich, and gut microbiota. We divided the experimental data into three groupings based on the given scores: The first group consisted of genes with score s < −3, where the gene knockout could be considered essential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation